Policies in Higher Education: The Impact of Global Trends on the Operation of the South African Universities - Masenya, Malesela (EDUCATIO : Journal of Education, 2023)
The purpose of this paper is to locate and discuss the policies that governs South African universities in relation to the global trends and their impacts thereof. The higher education system in South Africa is shaped and understood according to many different narratives, the story of higher education globally, and the fundamental changes it has undergone, its own particular history and legacy told from many perspectives, and the deliberate steering of the system through the application of policy drivers to reach particular goals. Intricately intertwined with the society in which it is embedded, the higher education sector in South Africa today is as much a creature of its past as it is a creature of sustained effort, through policy, legislation and institutional restructuring, to redirect and transform it. In higher education, there is an increasing resultant standardisation of the curriculum in response to the market forces. Politics in the age of globalisation should not be seen as a practice of noble hopelessness because there a rapid expansion of a global higher education market, based on the discourse of global competition. The paper argues that that while the South African higher education system has experienced considerable growth, this growth has not been met with sufficient funding to enable the national goals of higher education to be fully met, and the prospects of a sustainable increase in funding are negligible. The higher education system in South Africa is undoubtedly under pressure, due to a number of institutions struggling to keep the higher education project alive. The paper concludes that, in order to become internationally competitive, national policies in developing countries tends to use key projects to drive reform processes, and establish priorities, and is focusing investment on a few universities. Institutional managements and staff have to deliver on sometimes competing objectives.